More benefit or harm? Moral contextualism shapes public attitudes towards social egg freezing - Forke, Anna; Siegers, Pascal (Frontiers in Political Science, 2022)
Medical treatments at the beginning and end of human life are highly contested in public discourse. Our study reveals factors shaping the acceptance of social egg freezing (or oocyte cryopreservation) as an assisted reproduction technology (ART) in the general public. Based on the theory of moral contextualism and the literature on medical ethics, we deduce potential factors influencing attitudes toward cryopreservation (for example, the number of oocytes used or the age up to which women plan to use the oocytes). The influence of these factors on individual attitudes is modeled using a factorial design embedded into a web survey. The results show that factors associated with potential harm to the children decrease acceptance of cryopreservation, whereas factors associated with potential harm to the women increase acceptance. The strongest effect has the age at which women plan to use the preserved oocytes.